Impact of surgical margin clearance for resection of secondary hepatic malignancies. Issue 3 (10th December 2015) - Bhutiani, Neal; Philips, Prejesh; Martin, Robert C.G.; Scoggins, Charles R.
Abstract : Over the past several decades, there has been increasing discussion regarding the optimal management of secondary liver malignancies. Traditionally, resection has only been recommended if it could be accomplished with negative microscopic margins of at least 10 mm. However, many investigators have pushed this limit to offer resection to patients with narrower margins. We review the data regarding the impact of margin clearance on outcomes for patients undergoing hepatic metastasectomy. J. Surg. Oncol. 2016;113:289–295 . © 2015 Wiley Periodicals, Inc.